HAMZAH أPREFIXANDGEMINATION ــّــOFFI’L TSULATSY MAZID IN ARABIC: CASE STUDY FROM SURAH AL BAQARAH - Khoirin Nikmah (Universitas Muhammadiyah Lampung, 2021)
This research focused on hamzah أ prefix and gemination ــّــ of fi’l tsulatsy mazid in Arabic: Case study from surah al baqarah. It was aimed to describe: (1)hamzah prefix and gemination of fi’l tsulatsy mazid’s distributions from surah al baqarah; (2) meaning from their distributions. The approach applied in this research is descriptivequalitative. Meanwhile, the method of collecting data is observation method with recording andtaking note technique.According to the number of data, there are five formulas found related to prefix hamzah أ and gemination ــّــ.In this case, hamzah أ prefixfrom surah al baqarahmight be distributeto verb, noun, adjective, andadverb. Then, geminationــّـmight be distribute to verb, noun, and adjective. Furthermore, there was one similarity between them. Either hamzah prefix or gemination has benefactive meaning when it was distributed to verb, noun, and also adjective.